DEVELOPMENT MANAGEMENT OF THE LLC «GAZPROM ENERGOKHOLDING»: ENVIRONMENTAL ASPECT - E. Kamchatova (Вестник университета, 2018)
The purpose of the article is to identify the companies of LLC «Gazprom energokholding» main measures aimed at reducing the cost of compensation for damage from negative environmental impact of energy facilities. The subject of the research is the investment program of development, which constitutes a set of investment projects and solutions aimed at improving the effciency of production and economic activities of companies taking into account environmental aspects. The article analyses the environmental activities of the objects of LLC «Gazprom energokholding», which is one of the largest suppliers of energy in the electricity and power markets.